0827 Bedtime Routines, Nighttime Awakenings and Sleep in Low-Income Toddlers. (27th April 2018) - Covington, L B; Armstrong, B; Black, M M
Abstract: Introduction: Implementing a bedtime routine (pre-bedtime activities) has been linked to better sleep quality among toddlers, though the mechanism of this association is unclear. Limited research has examined the relationship between bedtime routines and sleep duration among low-income African American families; a population at increased risk of poor sleep. This study examined the associations between bedtime routines, nighttime awakenings and nighttime sleep duration in a sample of low-income toddlers. We hypothesized that implementing a bedtime routine would be associated with an increase in nighttime sleep duration through decreased nighttime awakenings. Methods: The sample included 118 low-income mother-toddler dyads recruited from a primary care clinic. Mothers completed the Brief Infant Sleep Questionnaire (BISQ) reporting how often they implemented a bedtime routine, how often their child woke up during the night, and their child's sleep duration over the past two weeks. A path analysis was conducted in Mplus Version 6.11 to investigate whether number of awakenings mediated the relation between bedtime routines and nighttime sleep duration, controlling for toddler age. Results: The sample was 95% African American, 95% had public or no insurance, and 55% implemented a bedtime routine every night. Toddlers slept an average of 9 hours/night and woke up an average of 1 time per night. Implementing a bedtime routine was associated with fewer nighttime awakenings (β = -0.684, p = <.001). One extra nighttime awakening was associated with 39 minutes less sleep (β = -39.116, SE = 12.140, p = .001). There was a significant indirect effect of nighttime awakenings on the relation between bedtime routine and nighttime sleep duration (β = 26.741, 95% CI = 8.670, 47.671 p = .026). Conclusion: Nighttime awakenings mediated the relation between implementing a bedtime routine and nighttime sleep duration for toddlers. Future research should investigate strategies to adopt and consistently implement bedtime routines in low-income families to ultimately improve toddler sleep. Support (If Any): Sigma Theta Tau International Honor Society of Nursing, Pi Chapter, Doctoral Student Research Award.